‘Public prostitutes and private prostitutes’: A study of women's perceptions of transactional sex in Cameroon - Lépine, Aurélia; Henderson, Charlie; Nitcheu, Emile; Procureur, Fanny; Cust, Henry; Toukam, Létitia; Chimsgueya, Chimene; Noo, Julienne; Szawlowski, Sandie; Tamgno, Eric Defo; Mandop, Silvia; Moyoum, Stephanie; et al. (Social science & medicine (1982), 2024)
Although AIDS-related deaths continue to decline, there are more people living with HIV than ever before. Sub-Saharan Africa remains disproportionately affected by the epidemic, with women aged 15–24 being over three times as likely to acquire HIV than their male counterparts. One reason for this disparity is that those engaging in ‘transactional sex’ do not benefit from governmental HIV prevention efforts. Transactional sex is both less well understood than sex work and more common, suggesting the need for further research. To this end, we interviewed eighteen women engaging in transactional sex in Yaoundé, Cameroon using snowball sampling. Participants were recruited using respondent-driven sampling, with the help of a nongovernmental organisation that works with women engaging in transactional sex. The objective of this study is to understand how transactional sex differs from commercial sex according to women engaging in transactional sex. We found that participants distinguished themselves from sex workers, but only in a limited sense. They referred to themselves as ‘private prostitutes’, meaning those who sell sex in all but name. ‘Private prostitutes’ avoid red-light districts and do not wear revealing clothing, but exchange sex for money all the same. They are no less profit-oriented than their ‘public’ counterparts (i.e., sex workers), reminding us that the two activities have a lot of similarities in as far as public health is concerned. Women engaging in transactional sex would require equal attention than FSWs in terms of HIV prevention. Like FSWs, they have multiple sexual partners and unprotected sex. They should be considered a ‘key population’ for HIV prevention. This would improve public health outcomes, suggesting the need to target women engaging in transactional sex on a greater scale than previously attempted in Sub-Saharan Africa. •Transactional sex is both less well understood and more prevalent than sex work.•We conducted qualitative research to explore perspective of transactional sex.•Women engaging in transactional sex referred to themselves as ‘private prostitutes’.•Transaction sex appeared to be as risky as sex work in terms of HIV.•Women in transactional sex should receive national HIV prevention programmes.